2014
DOI: 10.1016/j.exer.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Retinal macroglia changes in a triple transgenic mouse model of Alzheimer's disease

Abstract: The retinas of Alzheimer’s disease (AD) patients and transgenic AD animal models display amyloid beta deposits and degeneration of ganglion cells. Little is known, however, about the glial changes in the AD retina. The present study used a triple transgenic mouse model (3xTG-AD), which carries mutated human amyloid precursor protein, tau, and presenilin 1 genes and closely mimics the human brain pathology, to investigate retinal glial changes in AD. AD cognitive symptoms are known to begin in the 3xTG-AD mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 45 publications
(75 reference statements)
6
45
0
Order By: Relevance
“…In line with the above findings, numerous studies examining the retinas of sporadic and transgenic animal models of AD have reported Aβ deposits, vascular Aβ, pTau, and paired helical filament-tau (PHF-tau), often in association with RGC degeneration, local inflammation (i.e., microglial activation), and impairments of retinal structure and function (11,39,40,42,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). These studies, which included a variety of transgenic rat and mouse models, as well as the sporadic rodent model of AD, Octodon degus, demonstrated abundant Aβ deposits, mainly in the innermost retinal layers (RGCs and NFL) (40,42,45,49,52,54,57).…”
Section: Introductionmentioning
confidence: 80%
“…In line with the above findings, numerous studies examining the retinas of sporadic and transgenic animal models of AD have reported Aβ deposits, vascular Aβ, pTau, and paired helical filament-tau (PHF-tau), often in association with RGC degeneration, local inflammation (i.e., microglial activation), and impairments of retinal structure and function (11,39,40,42,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). These studies, which included a variety of transgenic rat and mouse models, as well as the sporadic rodent model of AD, Octodon degus, demonstrated abundant Aβ deposits, mainly in the innermost retinal layers (RGCs and NFL) (40,42,45,49,52,54,57).…”
Section: Introductionmentioning
confidence: 80%
“…These include the Tg2576, APP/PS1, 3xTg, 5xFAD mice, the TgF344-AD rat, and O. degus [1, 4648, 107, 117, 134, 148, 150, 152, 154, 178, 184]. It has been reported that levels of Aβ 40 and particularly Aβ 42 are elevated in the retina, as well as in the lens, vitreous humor, and choroid of AD rodent models (Table 2) [1, 46, 47, 117, 148, 150, 154, 178, 184].…”
Section: Ad-specific Ocular Pathology In Animal Modelsmentioning
confidence: 99%
“…Deposits of insoluble Aβ species and subsequent plaque formation have been documented in the retinas of Tg2576, APP SWE /PS1 ΔE9 , APP SWE /PS1 M146L/L286V , 3xTg, and 5xFAD mice, as well as O. degus [1, 4648, 107, 108, 117, 134, 139, 152, 184, 187, 188]. In the Tg2576 mouse, plaques have been identified most consistently in retinal layers ranging from the GCL to the ONL, and rarely in the photoreceptors and optic nerve [117, 184].…”
Section: Ad-specific Ocular Pathology In Animal Modelsmentioning
confidence: 99%
“…The immunoreactivity of glial fibrillary acidic protein, usually used as a marker of gliosis, is increased in the ganglion cell layer of retinas from AD patients [69]. Moreover, increased retinal macroglia reactivity, reported as reactive morphology and increased number of astrocytes, was described in a triple transgenic animal model of AD [90]. Regarding microglia, increased expression of MHC II (a marker of microglial reactivity) was described in the retina of AD patients [91].…”
Section: Can Retinal Glia-mediated Neuroinflammation Be Used As a Marmentioning
confidence: 99%